The new "minimum vital income" in Spain: Distributional and poverty effects in the presence and absence of regional minimum income schemes - Nuria Badenes Plá; Borja Gambau-Suelves (University of Essex, Institute for Social and Economic Research (ISER), 2020)
The "Minimum Vital Income" (IMV) constitutes a novelty in the panorama for fighting poverty by guaranteeing minimum incomes after the COVID-19 crisis. This work simulates the distributional and poverty effects of the IMV introduction across Spanish regions using EUROMOD. Our results show that the IMV reduces inequality and poverty - general and extreme - for all regions. The regional minimum income schemes (RMI) have been a fundamental measure to fight poverty in Spain from the regional level, although this power has not been as effective as it was expected in reducing inequality. This work also simulates the effects on inequality and poverty that the elimination of current RMI and the introduction of the new IMV would generate. Considering the simultaneous introduction of IMV and RMI elimination, the negative effects of RMI would be offset by positive effects of IMV, leading also to a big additional saving for the Spanish Public Accounts.
Keywords: C81; D63; D31; I32; H24; 330; microsimulation; inequality; income distribution; poverty; minimum vital income; EUROMOD